Analisis Penyebab Produk Defect Selama Penyimpanan pada Perusahaan Manufaktur Plastik dengan Diagram Pareto dan Root Cause Analysis - Sinaga, Tuti Sarma; Budiman, Irwan; Kartika, Tengku Heny (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research was conducted in a factory that produces polypropylene, polyethylene, and high density plastics located in North Sumatra Province, Indonesia. Based on the characteristics of its products, the company implements a make to stock system. However, the products experience quite high damage reaching 20% ​​of its total production. Therefore, this study will analyze the causes of defective products during storage in a plastic factory. In this study, historical data of damage that occurred and Pareto Diagram were used to obtain the main causes and analyze them so that defective products when stored in the warehouse can be reduced. Based on the Pareto Diagram, it was found that sticky and discolored plastics dominate the number of defective products. To prevent this, it is necessary to manage the temperature of the storage room, provide a good understanding for operators and inspect materials according to standards